Validation of the Malay version of affiliate stigma scale among caregivers of patients with mental illness in Hospital Universiti Sains Malaysia - Yun, Yap Siau (2018)
Background: Caregivers of a patient with mental illness are exposed to stigma. The internalization of this self-stigma among caregivers is known as affiliate stigma. Affiliate Stigma Scale was different compared to other tools used to measure the stigma among caregivers as it measures the internalization response related to the perceived stigma from surrounding. Nevertheless, there is lack of information on the psychometric properties of this tool used in the Malaysia context. The objective of this study was to validate the Malay version of Affiliate Stigma Scale. Methods: A cross-sectional study, involving 372 caregivers of a patient with mental illness, was conducted from May to December 2017, at psychiatry clinic hospital USM. ASS was first translated into Malay language using standard forward and backward translation procedures by a group of experts. Participants then completed the ASS-Malay (ASS-M). The data analyses involve assessment of construct validity by exploratory factor analysis, confirmatory factor analysis and construct reliability. Results: Our final model of ASS-Malay (ASS-M) consists of four factors with 21 items, as compared to original version with three factors with 22 items. Our finding showed the final model has good model fit based on RMSEA (0.065) and SRMR (0.055) and satisfactory composite reliability (Affective = 0.827, Cognitive = 0.857, Behaviour = 0.764, Self-Esteem = 0.861). Conclusion: The study showed that the four-factor model with 21 items of the Malay version of ASS has good psychometric properties. The scale is valid and reliable to measure affiliate stigma among caregivers of a patient with mental illness in Malaysia.